Development of chemical element interpreter using Augmented Reality (AR) Technology (Non-Metal) - Quion, Richard F., author; Romero, Renielyn S., author; Table, Shara Jane B., author; Estonilo, Christopher G., adviser; Nabablit, Karlo Jose E., technical critic (Rosario, Cavite : Cavite State University-CCAT Campus, 2016)
Thesis Abstract
A Design Project (BSInfoTech) -- Cavite State University-CCAT Campus, 2016.
Includes bibliographical references and appendices.
In English text.
Keywords: Augmented reality; Application software -- Development; Web application; Chemical elements; Chemical elements -- Databases; Periodic table of elements; E-learning.